Primer registro del género Anogramma Link (Pteridaceae) en Chile - HAHN, STEFFEN; GÓMEZ, PERSY (Gayana Botánica, 2018)
The genus Anogramma Link (Pteridaceae), by means of Anogramma leptophylla (L.) Link is reported for the first time in Chile, from a collection recently made in the Andes Mountains, Maule Region.